Perspektif Guru Taman Kanak-kanak Terhadap Pembelajaran Proyek Berbasis Bermain Dengan Pendekatan Playworld - Anita Yus; Handayani, Peny Husna; Artha Mahindra Diputera (Universitas Pendidikan Ganesha, 2023)
Learning for children at an early age refers to integrating learning through play. However, the need to integrate these concepts is a problem that still needs to be resolved in the literature. Apart from that, the conflict between parents' expectations for children and teachers' achievements is a complaint for kindergarten teachers in implementing play-based project learning with a Playworld approach, resulting in teachers' perceptions of this learning model. This research analyzes kindergarten teachers' perspectives on project learning through play with a Playworld approach. The sample for this research was 228 kindergarten teachers who were randomly selected using convenience sampling techniques. Questionnaires and FGDs were used to collect research data. Quantitative data was obtained by distributing questionnaires using Google Forms. Quantitative data was analyzed using descriptive analysis, and qualitative data was analyzed using thematic analysis. The research results show that kindergarten teachers have an average of 70.75 knowledge about project learning through playing with the Playworld approach, 69.09% experience using it, and 34.48% teacher creativity in using this learning. Based on these results, teachers experience difficulties integrating learning through play, especially play-based project learning with a Playworld approach. These findings have implications for improving the quality of learning and increasing teachers' abilities in designing and implementing better learning.